STEM-Based Mathematics Learning: Challenges and Opportunities in the Digital Age - Ramita Destiani; Fazila Maulida (LOGIKA: Jurnal Pendidikan Matematika, 2026)
Mathematics learning in the digital era faces complex challenges along with the demands of mastering 21st-century skills. One approach deemed relevant to address these challenges is STEM (Science, Technology, Engineering, and Mathematics)-based learning. This approach emphasizes interdisciplinary integration, contextual problem-solving, and the use of technology in the learning process. This study aims to analyze the challenges and opportunities for implementing STEM-based mathematics learning in the digital era. The method used was a systematic literature review of national and international journal articles published in the last ten years. The results of the study indicate that STEM-based mathematics learning has great potential to improve students' conceptual understanding, critical thinking skills, creativity, and numerical literacy. However, its implementation still faces various obstacles, such as limited teacher competency, technological infrastructure readiness, and suboptimal curriculum integration. Therefore, strengthening strategies are needed through teacher professional development, policy support, and the provision of equitable digital learning facilities.